STABILISASI TANAH LIAT DENGAN KAPUR PADA KONSTRUKSI BADAN JALAN HUTAN DI PULAU LAUT - Rahardjo S Suparto; S Sutopo (Jurnal Penelitian Hasil Hutan, 1984)
Subgrade  construction is an important part in forest  road building,  Subgrade soils with a high clay content  could  not be used satisfactorily as forest  road construction material  unless it is treated  to increase its stability.  The improvement of the  physical characteristics of clay  soils  related  to  subgrade  construction  can  be achieved  by  mixing  lime  of certain proportion into   the soil. The purpose of this investigation  is to determine the amount  of lime required for subgrade stabilization  which  have high clay content  in Pulau Laut,  South  Kalimantan The investigation  reveals the following :1.  The  efective  amount   of  lime  stabilization of  soils  is 7 percent of  the dry  weight  of  the  soil, resulting  in the following  physical  properties  :-  Bearing capacity  is 167 kg/cm2 at air dry  condition,-  Percent  of swell is 2.3,-  Plasticity index  is 25.5,  and-  pH is 9.00.2.  Stabilization   with  7 percent  lime is most  effective  for use in forest  road subgrade containing  about  66% clay.